2002
DOI: 10.1159/000047768
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Brainstem Diseases with Isolated Cranial Nerve Palsies

Abstract: There is a significant number of individual patients with cranial nerve palsies as the sole manifestation of MRI- and, less frequently, CT-documented small brainstem infarctions or hemorrhages. The 3rd and 6th nerves are most commonly involved and, less frequently, the 4th, 5th, 7th, and 8th nerves. An intra-axial basis for such lesions may be underestimated if the diagnosis is based solely on MRI. The electrophysiologic abnormalities indicating brainstem lesions may be independent of MRI-documented morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 60 publications
1
12
0
1
Order By: Relevance
“…PNS ischemia typically results from small-vessel occlusion of the vasa nervorum presenting as mononeuropathies, 63 most commonly related to vasculitis or diabetes mellitus. Isolated cranial neuropathies have previously been attributed to a mechanism similar to PNS ischemia but are now believed to result more commonly from MRI-defined microinfarcts in the brainstem 64 and are thus more similar to small-vessel infarctions. As a result of the differences in pathogenesis of ischemia between CNS and PNS ischemia, treatments for ischemia of the PNS and CNS differ.…”
Section: Definition Of Cns Infarction Should Be Limited To Cns Tissuementioning
confidence: 99%
“…PNS ischemia typically results from small-vessel occlusion of the vasa nervorum presenting as mononeuropathies, 63 most commonly related to vasculitis or diabetes mellitus. Isolated cranial neuropathies have previously been attributed to a mechanism similar to PNS ischemia but are now believed to result more commonly from MRI-defined microinfarcts in the brainstem 64 and are thus more similar to small-vessel infarctions. As a result of the differences in pathogenesis of ischemia between CNS and PNS ischemia, treatments for ischemia of the PNS and CNS differ.…”
Section: Definition Of Cns Infarction Should Be Limited To Cns Tissuementioning
confidence: 99%
“…In the subgroup analyses performed in the present study, isolated OCNP was identified as an independent risk factor for stroke even after adjusting for patient age and the presence of common cardiovascular risk factors such as HTN, diabetes, etc. Other possible mechanisms have been proposed, and these include roles for inflammation, infectious processes and hypercoagulability [6,8,25,26,27]. These factors were not evaluated in the present study, but would be factors to consider in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that vascular causes account for 20% of CN3 palsies, for 18.6% of CN4 palsies and for 17.7% of CN6 palsies [6]. Other etiologies such as aneurysm, trauma, neoplasm, brain stem infarction, infection, inflammation, sinus thrombosis and multiple sclerosis have also been proposed [7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…
We read with interest the review on cerebrovascular brainstem diseases with isolated cranial nerve palsies by Thömke et al [1]. They proposed to classify brainstem infarctions into three main categories: (1) classic ischemic brainstem syndromes with cranial nerve lesions and contralateral signs of the long tracts; (2) lacunar brainstem syndromes with isolated signs of the long tracts, and (3) cranial nerve brainstem syndromes whereby patients present with isolated cranial nerve palsy.
…”
mentioning
confidence: 99%
“…They proposed to classify brainstem infarctions into three main categories: (1) classic ischemic brainstem syndromes with cranial nerve lesions and contralateral signs of the long tracts; (2) lacunar brainstem syndromes with isolated signs of the long tracts, and (3) cranial nerve brainstem syndromes whereby patients present with isolated cranial nerve palsy. The authors reported that the case of brainstem vascular disorder with isolated 3rd nerve lesion is rare and that there have been only 36 cases documented in the literature.…”
mentioning
confidence: 99%